(untitled) (Damascus University Journal for legal sciences, 2025)
The principle of "binding force of the contract" is based on: contract may not be terminated or modified except by agreement of the parties or for reasons stipulated by law. However, the contract may be affected by cases that affect its economic balance. Exceptional accidents may create imbalances in the contract. In order to confront these cases, maybe parties renegotiate the contract, so they can include in the contract "condition of renegotiation", and this study explains the concept and provisions of this condition in the Syrian civil law and comparative law.